2008
DOI: 10.2527/jas.2007-0346
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of beef chuck and loin muscles with ammonium hydroxide and salt1,2

Abstract: ABSTRACT:The objective of this study was to evaluate the tenderness of beef chuck and round muscles when enhanced with ammonium hydroxide and salt at different pump levels. A randomized, complete block design of 4 treatments and 3 muscles with 3 replications was used, with a total of 15 subprimals per treatment. Treatments included a 0% (CON), 15% (T15), 22.5% (T22), and 30% (T30) target pump. The triceps brachii (TB), biceps femoris (BF), and rectus femoris (RF) muscles were studied. Muscles were injected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Hence, we speculate that a greater affinity of myoglobin for carbon monoxide, less oxidative stress due to anaerobic condition, and its effects on mitochondrial oxygen consumption may have improved the surface color of dark-cutting beef. In support, Hamling and Calkins (2008) reported CO-MAP improved appearance of ammonium hydroxideenhanced (high-pH) beef.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, we speculate that a greater affinity of myoglobin for carbon monoxide, less oxidative stress due to anaerobic condition, and its effects on mitochondrial oxygen consumption may have improved the surface color of dark-cutting beef. In support, Hamling and Calkins (2008) reported CO-MAP improved appearance of ammonium hydroxideenhanced (high-pH) beef.…”
Section: Discussionmentioning
confidence: 84%
“…When vacuum‐packaged, fermented beef snack sausages were stored for 30 to 90 days, Smith et al () reported that neither TBARS values nor sensory panel scores for cardboard flavor (indicative of lipid oxidation) were affected by including 5 to 20% LFTB in the sausage formulation. Interestingly, beef steaks enhanced with ammonium chloride were perceived to have fewer off‐flavors by both trained‐sensory and consumer panels (Hamling and Calkins ; Hamling et al . ), especially rancid flavors (Hamling and Calkins ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, beef steaks enhanced with ammonium chloride were perceived to have fewer off‐flavors by both trained‐sensory and consumer panels (Hamling and Calkins ; Hamling et al . ), especially rancid flavors (Hamling and Calkins ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that STPP aides in improving meat tenderness through dissociation of actomyosin (Bendall 1954; Hamm 1970). Although increased tenderness as measured by WBS Force has been observed when meat products were injected with ammonium hydroxide (Hamling and Calkins 2008; Hamling and others 2008), products were always compared to a noninjected control making it difficult to differentiate between tenderness being a result of increased moisture in the product or through the action of the ammonium hydroxide. It is possible the slightly higher pH of AHT steaks contributed to overcoming cook loss differences.…”
Section: Resultsmentioning
confidence: 99%
“…Ammonium hydroxide is considered a safe and suitable ingredient for increasing meat brines to pH 11.6 (USDA 2010). Several reports have indicated that the use of ammonium hydroxide in brines injected into fresh meat can increase tenderness and sensory ratings when compared to noninjected products (Everts and others 2006a, 2006b; Nath and others 2006; Hamling and Calkins 2008; Hamling and others 2008). However, all of these reports used a patented process for incorporating ammonium hydroxide into the brine and, aside from reporting final brine pH, brine formulation is not fully disclosed.…”
Section: Introductionmentioning
confidence: 99%